VD_FINDINFO HC / 2012 / 283 vom 4. April 2012 - VD Tribunal cantonal (2012)
RÉSILIATION IMMÉDIATE, TORT MORAL, CONTRAT DE DURÉE DÉTERMINÉE, CONTRAT DE DURÉE INDÉTERMINÉE | 337 CO, 337b CO, 337c CO, 49 CO, 308 CPC (CH), 310 CPC (CH), 311 CPC (CH), 313 CPC (CH), 405 CPC (CH)